Evaluation of Unique Mango Accessions for whole-Fruit Pickle - C Vasugi (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2008)
Studies conducted to evaluate the suitability of nineteen unique mango accessions for preparation of tender whole mango pickles revealed that these varieties were characterized by their acidic taste and rich raw mango flavour, which are most prefered for pickle production. The physical and quality parameters viz. fruit shape, weight, raw mango flavour, firmness, titrable acidity, latex flow, pH, dry matter and vitamin C which are important in pickle quality, showed wide variations among different varieties. Based on the sensory evaluation of whole immature green mango pickle prepared by standard fermentation and curing method, the accessions viz., Kashimidi, Isagoor Appe, Malange, Appemidi, Dantimamidi and Jeerige were considered to be most suitable for preparation of tender mango pickles.